Empowering Edmodo to Develop Oral Communication Skills of Nautical Student - Reham Ali El- Sayed Sobh (Faculty of Education - Port Said University, 2018)
The present study investigated the effectiveness of a treatment based on educational social networks (Edmodo) in developing some oral communication skills of first year Maritime Transport students, Arab Academy for Science, Technology and Maritime Transport (AASTMT). Edmodo was supported by short recorded speeches based on their terminology.  Forty  MTS navigation department were included  in the present study .The two- groups  quasi - experimental design was used. The educational social network site Edmodo was integrated along with face-to face sessions. The results of the study proved statistically significant difference between the mean scores of the experimental group and control group in the post-course administration of assessment tools. The obtained results imply the effectiveness of the treatment based on using educational social networks in teaching English for specific purposes in general and oral communication skills in particular.